Preparation of anion exchange magnetic beads for adsorbing endotoxin
By modifying SiO2 and functional silane coupling agent on the surface of the superparamagnetic nanoparticles of the anion exchange magnetic beads, and modifying aminosilane coupling agent, epoxy compounds and affinity ligands, a hyperbranched functional layer is formed, which solves the problems of complex process, low adsorption efficiency and non-specific adsorption risks in the prior art, and achieves efficient and economical endotoxin adsorption effect.
Patent Information
- Application Number
- CN202411838131.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
In the preparation of anion exchange magnetic beads, the process is complicated, the reagent cost is high, the post-treatment steps are complex, and a large amount of waste liquid is generated. The thin amine-based functional layer covered on the surface is at risk of iron ions leakage, the adsorption level is low and there is a risk of non-specific adsorption.
Superparamagnetic nanoparticles were prepared by thermal cracking, and SiO2 and functional silane coupling agent were modified on their surface. After modification, the surfactant amino groups were added. Then, epoxy compound modification and affinity ligands and small molecule amino compounds were modified to form a hyperbranched functional layer to improve adsorption capacity.
It realizes efficient adsorption of endotoxins, reduces the risk of non-specific adsorption, improves protein retention, and simplifies process and saves costs, which is suitable for fully automated operations.
Smart Images

Figure CN119702092A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano magnetic beads and modification thereof, and in particular to the preparation of anion exchange magnetic beads for adsorbing endotoxin. Background Art
[0002] Endotoxin is a general term for toxic substances present in the cells of Gram-negative bacteria (such as Salmonella typhi, Shigella dysenteriae, etc.), and is a component of the cell wall of many Gram-negative bacteria. The toxin released after the cell lysis is also called "pyrogen", with the unit of Eu / ml. Its chemical composition includes phospholipid polysaccharide-protein complex, and its toxic component is mainly lipid A. Endotoxin is located in the outermost layer of the cell wall, covering the mucopeptide of the cell wall. The toxic effects of endotoxins of various bacteria are weak and roughly the same, which can cause fever and microcirculatory disorders. Endotoxin is heat-resistant and stable, with weak antigenicity, and can stimulate the body to produce antibodies. Endotoxin is toxic to the host. Although endotoxin is tightly embedded in the cell wall, it will continue to release endotoxin to the surrounding environment. This release is not only caused by the disintegration and death of cells, but also occurs during normal cell growth and division. Endotoxin is not a protein, so it is very heat-resistant. It will not be destroyed even if heated at 100℃ for 1 hour. Its biological activity can only be destroyed by heating at 160℃ for 2 to 4 hours, or boiling with strong alkali, strong acid or strong oxidant for 30 minutes.
[0003] The development of appropriate endotoxin removal schemes and materials is of great significance for protecting humans and other living organisms. The endotoxin removal materials prepared in the currently disclosed technical schemes mainly include polymers and polymer microspheres as carriers to modify affinity ligands, hydrophilic gel microspheres to modify ion exchange ligands, anion exchange resins, centrifugal columns, and magnetic beads.
[0004] Affinity ligands modified on polymer microspheres can be used for adsorption and removal of endotoxins. For example, Jiangsu Beimei Medical Technology Co., Ltd. uses chitosan microspheres, aminated polystyrene microspheres or aminated polyvinyl alcohol microspheres as carriers to modify adsorption ligands in patent CN 114225919 A; Sito Sol Benz uses cross-linked polystyrene microspheres modified with polyols as carriers in patent CN 109562353A; Tianjin Yunus Biotechnology Co., Ltd. uses porous spherical polymer material polyvinyl alcohol-triallyl isocyanurate copolymer as carrier to modify aliphatic diamine for blood perfusion removal of endotoxins in patent CN 103406111 A; Nankai University uses polymethyl methacrylate as carrier in patent CN 1528511 A and prepares endotoxin adsorbent by modifying cationic ligands in two steps.
[0005] In order to improve the hydrophilicity and biocompatibility of the endotoxin adsorbent, several water-soluble polymers are preferably used to prepare carriers and further couple ligands. For example, Dalian University of Technology used agarose gel containing hydroxyl groups as a carrier to modify quaternary ammonium salt cations and hydrophobic molecules at the same time in CN 101157018 A, and prepared an endotoxin adsorbent material for the treatment of endotoxemia; Zhuhai Jianfan Biotechnology Co., Ltd. prepared an endotoxin synergistic adsorbent in CN 10258683A, and the carrier selection included cellulose, agarose, polyvinyl alcohol, styrene-divinylbenzene copolymer or polymethyl methacrylate, preferably hydrophilic cellulose and polymethacrylic acid, and cellulose was used as a more preferred carrier. The main reason is that cellulose has relatively high mechanical strength and toughness; has good biocompatibility and good safety; is rich in sources and low in cost; is environmentally friendly and can be naturally degraded after use. Sodium deoxycholate is first modified on a hydrophilic carrier and then a cationic compound is modified to achieve a synergistic effect. In CN 105664868A, Guangzhou Kangsheng Biotechnology Co., Ltd. uses spherical natural polymers with a particle size of 0.05-1.5 mm as carriers, including chitosan microspheres, agarose gel, dextran gel or cellulose microspheres, and obtains active carriers through diglycidyl ether coupling, which are then coupled with amino-containing ligands to prepare endotoxin adsorption materials; Chongqing Hillcon Blood Purification Equipment R&D Co., Ltd. uses a cross-linking agent to modify soluble starch to obtain starch microspheres in CN 117986664 A, then fixes endotoxin affinity peptides on the starch microspheres, and finally blocks them with BSA.
[0006] One of the mainstream methods for endotoxin adsorbents to act on endotoxins is based on anion exchange. For example, Li Tao used anion exchange resin as an adsorbent to treat endotoxemia in CN101642591 A. This method removes endotoxins through blood / plasma perfusion, and the adsorption rate of endotoxins can reach more than 90%; ThermoFisher Detoxi-Gel TM endotoxin removal gel is an agarose resin modified with the affinity ligand polymyxin B; GenScript ToxinEraserTM endotoxin removal kit is a resin modified with the affinity ligand polymyxin B. The main mechanism of action of this type of product is affinity chromatography and electrostatic adsorption.
[0007] Centrifugal columns for removing endotoxins have also been commercialized. For example, Beijing Quanshijin Biotechnology Co., Ltd. disclosed a plasmid DNA extraction kit for removing endotoxins in CN117603960 A, which includes a plasmid extraction centrifugal column, the column membrane component of which is a silicon matrix membrane with a pore size of 5-40 μm; the ThermoFisher PierceTM high-capacity endotoxin removal centrifugal column can reduce the endotoxin level in a protein sample to less than 1% within 1 hour, and the protein recovery rate is greater than 85%.
[0008] Since the above methods are difficult to meet the requirements of automated operation, magnetic bead-based solutions have also been gradually developed. For example, the Institute of Sensor Technology of Gansu Academy of Sciences used nickel magnetic beads coupled with polyhistidine ligands in CN 117925602 A, with a particle size of 0.5-1 μm, for the extraction of endotoxin-free plasmids. Compared with a variety of endotoxin removal kits, the magnetic bead method can ensure a high plasmid yield while also ensuring an endotoxin removal efficiency that is superior to that of the kit; Changzhou Hongmeng Biotechnology Co., Ltd. recombinantly expressed the C factor of the Oriental horseshoe crab and coupled it to polymer magnetic beads in CN 115876545 A. When used to remove endotoxins from proteins, the endotoxin level can be reduced to 0.25 EU / mL, and the protein recovery rate is greater than 95%; Guangzhou Boren Ankang Medical Technology Co., Ltd. coupled amino acid fragments that can specifically bind to endotoxins to agarose magnetic beads in CN 112742067 A, which can reduce the endotoxin level to less than 1% while maintaining a protein recovery rate of more than 95%; Guangzhou Bay Area Biotechnology Co., Ltd. in CN 111088248 In A, quaternary ammonium salt is first cationized and modified onto the surface of hydroxyethyl cellulose magnetic microspheres for the removal of endotoxins in plasmids, with a high plasmid yield; Zhejiang University of Technology described the preparation of magnetic chitosan microspheres and their application in the adsorption of endotoxins in CN 102423721 A; Kangma Biotechnology Co., Ltd. introduced a method for preparing endotoxin-removing magnetic beads by binding polymyxin to carboxyl magnetic beads in CN 115722205 A.
[0009] 1. The prior art preparation of anion exchange magnetic beads is cumbersome, the reagent cost is high, the post-processing steps are numerous and complicated, and a large amount of waste liquid is generated; for example, in CN 102423721 A, acetic acid, liquid paraffin containing Span 80 and petroleum ether are used as solutions, formaldehyde and epichlorohydrin are used as cross-linking agents, and ethanol is used as a detergent. The reagent dosage is large and contains hazardous chemicals.
[0010] 2. The amino functional layer coated on the surface of anion exchange magnetic beads prepared by the prior art is relatively thin, and there is a risk of iron ion leakage and magnetic bead leakage. For example, in the preparation of hydroxyethyl cellulose magnetic beads in CN 111088248 A, hydroxyethyl cellulose is only physically adsorbed on the surface of the magnetic core, and then the hydroxyethyl cellulose is cross-linked with epichlorohydrin to fail to completely seal the magnetic core in the functional layer, which has a risk of leakage.
[0011] 3. The anion exchange magnetic beads prepared by the prior art have a low level of endotoxin adsorption and a large amount of non-specific adsorption risk. The magnetic microspheres prepared in the discussion of CN 102423721 A have a removal rate of 77.5% for endotoxin in acidic proteins and a protein retention rate of 76.8%. The endotoxin removal efficiency is low and cannot meet the direct use requirements of downstream proteins. Therefore, we propose a preparation of anion exchange magnetic beads for endotoxin adsorption. Summary of the invention
[0012] 1. Technical issues to be resolved
[0013] In view of the deficiencies in the prior art, the present invention provides a method for preparing anion exchange magnetic beads for adsorbing endotoxin, thereby solving the technical problems raised by the background art.
[0014] (II) Technical solution
[0015] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0016] A preparation method of anion exchange magnetic beads for adsorbing endotoxins comprises the following steps:
[0017] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0018] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol or anhydrous triethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300r / min for 8h, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water;
[0019] (2) Disperse 2 g of the magnetic microspheres obtained in step (1) in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, stir for 10 min while ultrasonicating, transfer to a water bath and heat to 60° C., add 2 mL of tetraethyl orthosilicate and react for 1 h, then add 2 mL of 3-(3-aminopropyl)triethoxysilane and continue to react for 3 h. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol by magnetic separation, and wash them six times with water by magnetic separation;
[0020] (3) Disperse 1 g of the magnetic microspheres obtained in step (2) in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide into a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:1 to 1:0.1:5, heat to 80°C and react for 10 h. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol by magnetic separation, and wash them six times with water by magnetic separation;
[0021] (4) Disperse 1 g of the magnetic microspheres obtained in step (3) in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, add ethylenediamine, the mass ratio of magnetic beads to ethylenediamine is 1:1 to 1:5, and heat to 80°C for 8 h. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol, and wash them six times with water;
[0022] (5) Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and place it in a 2 mL centrifuge tube. Add 10 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use a Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample.
[0023] (III) Beneficial effects
[0024] The core-shell anion exchange magnetic beads of the present invention use Fe3O4 microspheres with high saturation magnetic strength as base microspheres, which have superparamagnetism and excellent magnetic response performance, so that they can be quickly separated in an external magnetic field. The technology of modifying SiO2 and functional silane coupling agents on Fe3O4 microspheres is quite mature. After modification with aminosilane coupling agents, the surfaces of the microspheres can be provided with active amino groups, which is convenient for subsequent modification of polymer layers and functional ligands. Epoxy monomers have high reactivity with amino groups, and can be quickly coupled to the surface of the amino Fe3O4 microspheres to generate secondary amine groups and hydroxyl groups. The secondary amine groups and hydroxyl groups can continue to react with epoxy monomers in the presence of a strong alkaline catalyst to induce a chain reaction to generate branched polymers. The polyepoxy monomers make the branched polymers carry abundant epoxy functional groups. The abundant epoxy groups and the longer spacer arms can be grafted with more affinity ligands and small molecule amino compounds, which greatly increases the amount of affinity ligands and the amino content per unit mass on the surface of the magnetic beads. The affinity ligands play an affinity role and bind to endotoxins, and the small molecule amino groups increase the positive charge content of the magnetic beads and enhance the electrostatic effect. In addition, the longer spacer arms and branched structures provide good steric hindrance, making it difficult for impurities in the sample to bind, thereby improving the specificity of endotoxin adsorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.
[0026] Figure 1 Schematic diagram of the preparation principle of anion exchange magnetic beads;
[0027] Figure 2 Transmission electron microscopy image of amino magnetic beads prepared by adding aminosilane coupling agent;
[0028] Figure 3 Transmission electron microscopy image of anion exchange magnetic beads prepared by adding aminosilane coupling agent;
[0029] Figure 4 This is a transmission electron micrograph of anion exchange magnetic beads prepared without adding aminosilane coupling agent. DETAILED DESCRIPTION
[0030] The embodiments of the present application solve the problems of anion exchange magnetic beads in the prior art by providing a method for preparing anion exchange magnetic beads for adsorbing endotoxin. The prepared anion exchanger uses superparamagnetic microspheres as carriers, which can achieve fully automated operation compared with fillers and filter membranes, saving labor costs and time.
[0031] In view of the problems existing in the prior art, the present invention provides a preparation method of anion exchange magnetic beads for adsorbing endotoxin, and the specific steps are as follows:
[0032] 1. First, superparamagnetic magnetic microspheres with uniform particle size and good magnetic properties are prepared by thermal cracking method;
[0033] 2. The second step is to coat SiO2 and different amino silane coupling agents on the surface of the magnetic microspheres in a mixed solvent of water and ethanol;
[0034] 3. In the third step, the aminosilane-modified magnetic beads are dispersed in a polar aprotic solvent (such as DMSO, THF, DMF, NMP, ACN), and hyperbranched epoxy functionalized magnetic beads are prepared in the presence of a strong alkaline catalyst. The surface is a hyperbranched functional layer and contains abundant epoxy groups; the schematic diagram is as follows Figure 1 ;
[0035] 4. Use different amine compounds to open the epoxy ring to prepare amine magnetic beads;
[0036] 5. Amine magnetic beads were used to adsorb endotoxins in proteins and the protein retention rate and endotoxin removal efficiency were determined.
[0037] Example 1
[0038] The technical solution in the embodiment of the present application is to solve the problems of the above-mentioned anion exchange magnetic bead process, and the overall idea is as follows:
[0039] In view of the problems existing in the prior art, the anion exchange magnetic beads of the present invention have superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0040] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0041] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0042] (2) Modified aminosilane coupling agent
[0043] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0044] (3) Modified Epoxy Compounds
[0045] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0046] (4) Modification of affinity ligands and small molecule amino compounds
[0047] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polylysine hydrochloride, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed 6 times with water;
[0048] (5) Testing the ability of magnetic beads to remove endotoxin
[0049] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0050] Example 2
[0051] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0052] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0053] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0054] (2) Modified aminosilane coupling agent
[0055] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask. The mixture was stirred for 10 min while ultrasonicating. The mixture was transferred to a water bath and heated to 60° C. 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added. After reacting for 1 h, 2 mL of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out and washed three times with anhydrous ethanol by magnetic separation and six times with water by magnetic separation.
[0056] (3) Modified Epoxy Compounds
[0057] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0058] (4) Modification of affinity ligands and small molecule amino compounds
[0059] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polylysine hydrochloride, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed 6 times with water;
[0060] (5) Testing the ability of magnetic beads to remove endotoxin
[0061] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0062] Example 3
[0063] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0064] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0065] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0066] (2) Modified aminosilane coupling agent
[0067] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0068] (3) Modified Epoxy Compounds
[0069] 1 g of the magnetic microspheres obtained in step (2) was dispersed in 100 mL of NMP solvent, and propylene glycol triglycidyl ether and potassium methoxide were added to a three-necked flask, with the mass ratio of magnetic beads, potassium methoxide and propylene glycol triglycidyl ether being 1:0.1:5 respectively. The temperature was raised to 80° C. for reaction for 10 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed six times with water;
[0070] (4) Modification of affinity ligands and small molecule amino compounds
[0071] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polylysine hydrochloride, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed 6 times with water;
[0072] (5) Testing the ability of magnetic beads to remove endotoxin
[0073] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0074] Example 4
[0075] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0076] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0077] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0078] (2) Modified aminosilane coupling agent
[0079] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0080] (3) Modified Epoxy Compounds
[0081] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium tert-butoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours, take out the modified magnetic nanoparticles after the reaction is completed, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0082] (4) Modification of affinity ligands and small molecule amino compounds
[0083] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polylysine hydrochloride, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed 6 times with water;
[0084] (5) Testing the ability of magnetic beads to remove endotoxin
[0085] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0086] Example 5
[0087] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0088] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0089] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0090] (2) Modified aminosilane coupling agent
[0091] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0092] (3) Modified Epoxy Compounds
[0093] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0094] (4) Modification of affinity ligands and small molecule amino compounds
[0095] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polymyxin B was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polymyxin B, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed six times with water;
[0096] (5) Testing the ability of magnetic beads to remove endotoxin
[0097] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0098] Example 6
[0099] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0100] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0101] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0102] (2) Modified aminosilane coupling agent
[0103] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0104] (3) Modified Epoxy Compounds
[0105] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0106] (4) Modification of affinity ligands and small molecule amino compounds
[0107] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C for reaction for 6 h, 1,8-octanediamine was added, and the mass ratio of magnetic beads, polylysine hydrochloride and 1,8-octanediamine was 1:1:1. The reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed six times with water;
[0108] (5) Testing the ability of magnetic beads to remove endotoxin
[0109] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0110] Comparative Example 1
[0111] Comparative Example 1 Compared with Example 1, the functionalized magnetic beads were prepared without adding an aminosilane coupling agent, and the preparation method thereof included the following steps:
[0112] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0113] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0114] (2) Modification of SiO2
[0115] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask. The mixture was stirred for 10 min while ultrasonicating. The mixture was transferred to a water bath and heated to 60° C. 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added and reacted for 4 h. After the reaction was completed, the modified magnetic nanoparticles were taken out and washed three times with anhydrous ethanol by magnetic separation and six times with water by magnetic separation.
[0116] (3) Modified Epoxy Compounds
[0117] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0118] (4) Modification of affinity ligands and small molecule amino compounds
[0119] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, the temperature was raised to 80°C and reacted for 6 h, and then ethylenediamine was added, the mass ratio of magnetic beads, polylysine hydrochloride, and ethylenediamine was 1:1:1, and the reaction was continued for 8 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed 6 times with water;
[0120] (5) Testing the ability of magnetic beads to remove endotoxin
[0121] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0122] Comparative Example 2
[0123] Comparative Example 2 Compared with Example 2, anion exchange magnetic beads were prepared without adding affinity ligand polylysine hydrochloride, and the preparation method thereof included the following steps:
[0124] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0125] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0126] (2) Modified aminosilane coupling agent
[0127] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask. The mixture was stirred for 10 min while ultrasonicating. The mixture was transferred to a water bath and heated to 60° C. 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added. After reacting for 1 h, 2 mL of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out and washed three times with anhydrous ethanol by magnetic separation and six times with water by magnetic separation.
[0128] (3) Modified Epoxy Compounds
[0129] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0130] (4) Modification of small molecule amino compounds
[0131] Take 1 g of the magnetic microspheres obtained in step (3) and disperse them in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, add ethylenediamine, and the mass ratio of magnetic beads to ethylenediamine is 1:1. Continue the reaction for 8 h. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0132] (5) Testing the ability of magnetic beads to remove endotoxin
[0133] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0134] Comparative Example 3
[0135] Comparative Example 3 Compared with Example 2, anion exchange magnetic beads were prepared without adding small molecule amino compounds, and the preparation method thereof included the following steps:
[0136] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0137] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0138] (2) Modified aminosilane coupling agent
[0139] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask. The mixture was stirred for 10 min while ultrasonicating. The mixture was transferred to a water bath and heated to 60° C. 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added. After reacting for 1 h, 2 mL of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out and washed three times with anhydrous ethanol by magnetic separation and six times with water by magnetic separation.
[0140] (3) Modified Epoxy Compounds
[0141] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0142] (4) Modification of affinity ligands
[0143] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polylysine hydrochloride was added, and the temperature was raised to 80° C. for reaction for 6 h. The mass ratio of magnetic beads to polylysine hydrochloride was 1:1. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed six times with water;
[0144] (5) Testing the ability of magnetic beads to remove endotoxin
[0145] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0146] Comparative Example 4
[0147] Comparative Example 4 Compared with Example 5, anion exchange magnetic beads were prepared without adding small molecule amino compounds, and the preparation method thereof included the following steps:
[0148] The anion exchange magnetic beads of the present invention have an average particle size of 500 nm, uniform particle size, obvious surface shell layer, high modification efficiency, superparamagnetism, high surface amino content, good hydrophilicity, and a hyperbranched structure on the surface; the preparation method thereof comprises the following steps:
[0149] (1) Preparation of superparamagnetic nanoparticles by thermal pyrolysis:
[0150] Add ferric chloride hexahydrate and anhydrous sodium acetate to anhydrous ethylene glycol, add to a three-necked flask of corresponding volume, stir and ultrasonicate for 30 minutes, the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol (or anhydrous triethylene glycol) is 1:1:10, place the three-necked flask in a heating mantle, heat to 180°C, react at a stirring speed of 300 r / min for 8 hours, cool to room temperature naturally after the reaction is completed, wash three times with anhydrous ethanol magnetic separation, and wash six times with magnetic separation water to obtain superparamagnetic Fe3O4 microspheres;
[0151] (2) Modified aminosilane coupling agent
[0152] 2 g of the magnetic microspheres obtained in step (1) were dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol and added to a 250 mL three-necked flask, stirred for 10 min while ultrasonicating, transferred to a water bath and heated to 60° C., 2 mL of tetraethyl orthosilicate and 2 mL of ammonia water were added, and after reacting for 1 h, 2 mL of (3-aminopropyl) triethoxysilane was added and the reaction was continued for 3 h. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was performed and washed three times with anhydrous ethanol, and then washed six times with water by magnetic separation;
[0153] (3) Modified Epoxy Compounds
[0154] Take 1 g of the magnetic microspheres obtained in step (2) and disperse them in 100 mL of NMP solvent, add 1,4-butanediol diglycidyl ether and potassium methoxide to a three-necked flask, the mass ratio of magnetic beads, potassium methoxide and 1,4-butanediol diglycidyl ether is 1:0.1:5 respectively, heat to 80°C and react for 10 hours. After the reaction is completed, take out the modified magnetic nanoparticles, wash them three times with anhydrous ethanol magnetic separation, and wash them six times with water magnetic separation;
[0155] (4) Modification of affinity ligands and small molecule amino compounds
[0156] 1 g of the magnetic microspheres obtained in step (3) was dispersed in a mixed solvent of 50 mL of water and 50 mL of anhydrous ethanol, polymyxin B was added, and the temperature was raised to 80° C. for reaction for 6 h. The mass ratio of magnetic beads to polymyxin B was 1:1. After the reaction was completed, the modified magnetic nanoparticles were taken out, and magnetic separation was washed three times with anhydrous ethanol, and magnetic separation was washed six times with water;
[0157] (5) Testing the ability of magnetic beads to remove endotoxin
[0158] Take 1 mL of the nucleic acid sample extracted by the magnetic bead method and put it into a 2 mL centrifuge tube. Add 100 μL of the magnetic bead suspension (magnetic bead concentration 0.1 g / mL) obtained in step (4). Invert and mix for 5 min. Transfer the supernatant by magnetic separation to a new 2 mL centrifuge tube. Use Onedrop ultra-micro UV-visible spectrophotometer to test the nucleic acid concentration. Use horseshoe crab reagent to determine the endotoxin level of the sample according to the instructions of the horseshoe crab reagent.
[0159] in, Figure 1 It is a schematic diagram of the preparation principle of anion exchange magnetic beads. The aminosilane coupling agent takes (3-aminopropyl)triethoxysilane as an example, and the epoxy monomer takes 1,4-butanediol diglycidyl ether as an example.
[0160] Figure 2 It is a transmission electron micrograph of amino magnetic beads prepared by adding aminosilane coupling agent, i.e., a transmission electron micrograph of magnetic beads obtained in step (2) of Example 1. From the figure, it can be seen that SiO2 and aminosilane layers are obvious, the surface is smooth, the boundary is clear, and the thickness can reach tens of nanometers. The introduction of SiO2 can successfully coat a large amount of aminosilane coupling agent. The introduction of aminosilane layer can make the subsequent epoxy monomer react on the surface of magnetic microspheres and continue to grow the molecular chain in the presence of a strong alkaline catalyst.
[0161] Figure 3 The transmission electron micrograph of anion exchange magnetic beads prepared by adding an aminosilane coupling agent, i.e., the transmission electron micrograph of the magnetic beads obtained in step (3) of Example 1, shows that the introduction of epoxy monomer thickens the surface shell and further increases the particle size. However, as the grafting reaction proceeds, the reaction steric hindrance of the surface active functional groups greatly increases, so it is difficult to see the rough surface.
[0162] Figure 4The transmission electron micrograph of the anion exchange magnetic beads prepared without adding the aminosilane coupling agent, i.e., the transmission electron micrograph of the magnetic beads obtained in Comparative Example 1, can be seen from the figure that when the aminosilane coupling agent is not added, the thickness of the surface functional layer is very thin and the surface is also obviously rough. This is because the aminosilane coupling agent has a self-catalytic effect when co-modified with tetraethyl orthosilicate. SiO2 modification on the magnetic microspheres makes the microspheres firstly negatively charged, and then makes it easier for the aminosilane coupling agent with a positive charge to be modified on the surface. Without the participation of the aminosilane coupling agent, it is difficult to obtain a smooth and thick shell layer at a lower tetraethyl orthosilicate dosage. In addition, not adding the aminosilane coupling agent also makes the surface of the magnetic microspheres have no active groups, and it is impossible to react with the epoxy monomer to form a surface functional layer.
[0163] The magnetic beads prepared in each embodiment and comparative example were used to remove endotoxins from nucleic acids, and tested with horseshoe crab reagent, and the final concentration of negative indicators was used to indicate the ability of the magnetic beads to remove endotoxins.
[0164] Table 1 Comparison of the ability of magnetic beads prepared in each embodiment and comparative example to adsorb endotoxin and nucleic acid
[0165]
[0166]
[0167] Table 2 Endotoxin removal rate and nucleic acid retention rate of magnetic beads prepared in each embodiment and comparative example
[0168]
[0169] Beneficial effects:
[0170] 1. The anion exchanger prepared in this scheme uses superparamagnetic microspheres as carriers. Compared with fillers and filter membranes (such as DEAE-Sepharose), it can achieve fully automated operation, saving labor costs and time.
[0171] 2. The surface magnetic inertness content of the superparamagnetic microspheres prepared by this scheme is maintained at a certain level, below 20%, retaining good superparamagnetism, and the magnetism is stronger than that of the magnetic microspheres prepared by Ying Guoqing in CN 102423721 A;
[0172] 3. Existing anion exchangers have low endotoxin removal efficiency. For example, the DEAE-Sepharose product has an endotoxin removal efficiency of about 80%, and a retention rate of less than 5% for acidic proteins. The magnetic microspheres prepared in the CN 102423721A have an endotoxin removal rate of 77.5% in acidic proteins and a protein retention rate of 76.8%. The endotoxin removal efficiency is low and cannot meet the direct use requirements of downstream proteins.
[0173] 4. The existing anion exchangers have low universal application capabilities, high adsorption rates for acidic proteins, protein loss rates greater than 20%, nucleic acid loss rates greater than 30%, and unsatisfactory retention rates.
[0174] 5. The endotoxin-free magnetic beads prepared in this scheme not only have a high ability to remove endotoxins, but also have a low adsorption capacity for proteins and nucleic acids, which is mainly due to the hyperbranched structure and excellent hydrophilicity of the surface of the amino-based magnetic beads.
[0175] The technical feature of the present invention is that the surface is modified with small molecule amino compounds and amino-containing polymers at the same time, affinity chromatography and ion exchange are combined for the adsorption and removal of endotoxins, which greatly improves the removal efficiency of endotoxins and the protein retention rate;
[0176] The technical features of the present invention lie in its unique surface structure. The hyperbranched functional layer provides good steric hindrance, greatly reducing the nonspecific adsorption of proteins. The modified hyperbranched functional layer has excellent hydrophilicity, making it more friendly during endotoxin adsorption and removal. It is suitable for protein aqueous solutions and also for plasmid extraction.
[0177] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.
Claims
1. Anion exchange magnetic beads for adsorbing endotoxin, characterized in that: The magnetic beads are made of superparamagnetic Fe3O4 obtained by solvent thermal treatment as the core, SiO2 and aminosilane coupling agent are modified on the outer surface of the magnetic Fe3O4, and epoxy magnetic beads with a branched structure layer are prepared by a ring-opening reaction of epoxy monomer outside the aminosilane functional layer. The surface of the epoxy magnetic beads is modified with an affinity ligand and a small molecule amino compound at the same time. The modification method of SiO2 is as follows: The method comprises the following steps: the aminosilane coupling agent is one of (3-aminopropyl)triethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; the epoxy monomer is one of 1,4-butanediol diglycidyl ether, 1,2,7,8-diepoxyoctane, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, glycerol triglycidyl ether, neopentyl glycol diglycidyl ether, and triglycidyl meta-aminophenol; the affinity ligand is one of polylysine hydrochloride or polymyxin B; and the small molecule amino compound is one of ethylenediamine, 1,3-propylenediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,8-octanediamine, and p-phenylenediamine.
2. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: The anion exchange magnetic beads are prepared by the following steps: (1) First, ferric chloride hexahydrate and anhydrous sodium acetate are added to anhydrous ethylene glycol, and then added to a three-necked flask of corresponding volume, stirred and ultrasonicated, and the three-necked flask is placed in a heating mantle, heated and stirred, reacted for a period of time, and then naturally cooled to room temperature after the reaction is completed, and washed with anhydrous ethanol and water magnetic separation to obtain superparamagnetic Fe3O4 microspheres; (2) In the second step, a certain amount of Fe3O4 microspheres are dispersed in a mixed solvent of water and ethanol, tetraethyl orthosilicate and amino silane coupling agent are added to modify the magnetic beads, ammonia water is used as a reaction catalyst, the temperature is raised and stirred for reaction, and anhydrous ethanol and water magnetic separation and washing are used to obtain surface amino-modified Fe3O4 microspheres; (3) In the third step, a certain amount of aminosilane-modified magnetic beads are dispersed in a polar aprotic solvent, and an epoxy monomer is added in the presence of a strong alkaline catalyst to initiate a reaction to prepare epoxy-functionalized magnetic beads with a hyperbranched layer, the surface of which is a hyperbranched functional layer and contains abundant epoxy groups. The temperature is raised and stirred, and the reaction is continued for a period of time. After the reaction is completed, the temperature is naturally lowered to room temperature, and the beads are washed with anhydrous ethanol and water magnetic separation to obtain magnetic beads rich in epoxy groups on the surface; (4) A certain amount of epoxy magnetic beads are dispersed in a mixed solvent of water and ethanol, an affinity ligand is added, the temperature is raised for a period of time, and then a small molecule amino compound is added. After the reaction is completed, the temperature is naturally lowered to room temperature, and the beads are washed with anhydrous ethanol and water magnetic separation to obtain anion exchange magnetic beads.
3. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: The magnetic bead matrix is superparamagnetic Fe3O4, with a particle size of 350nm, and the surface is modified by a silane functional layer, an epoxy functional layer and an affinity and particle exchange layer, with a thickness of 20-60nm.
4. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: In the step (1), the mass ratio of ferric chloride hexahydrate, anhydrous sodium acetate and anhydrous ethylene glycol is 1:1:
10.
5. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: In the step (2), the mass ratio of Fe3O4 to the mixed solvent is 1 to 5:100, the amount of tetraethyl orthosilicate and aminosilane coupling agent used is a certain mass ratio of Fe3O4, and the mass ratio of tetraethyl orthosilicate, aminosilane coupling agent, and Fe3O4 is 1:0.5 to 5:
1.
6. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: In the step (3), the aprotic polar solvent is dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), N-methylpyrrolidone (NMP), acetonitrile (ACN), the strong alkaline catalyst is potassium methoxide, potassium tert-butoxide, sodium methoxide, sodium tert-butoxide, and the epoxy monomer is 1,4-butanediol diglycidyl ether, 1,2,7,8-diepoxyoctane, 3,4-epoxycyclohexyl methyl 3,4-epoxycyclohexyl carboxylate, propylene glycol triglycidyl ether, neopentyl glycol diglycidyl ether, and triglycidyl m-aminophenol.
7. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: The mass ratio of the amino magnetic beads to the polar aprotic solvent is 1 to 3:100, the amount of the medium-strong alkaline catalyst is based on the epoxy monomer, the mass ratio of the catalyst to the epoxy monomer is 1 to 2:100, the mass ratio of the epoxy monomer to the amino magnetic beads is 1 to 10:1, and the reaction temperature is 80 to 120°C.
8. The preparation of anion exchange magnetic beads for adsorbing endotoxin according to claim 1, characterized in that: In the step (4), the mass ratio of the epoxy magnetic beads to the mixed solvent is 1 to 4:100, the volume ratio of the mixed solvent water to ethanol is 1:1, and the mass ratio of the epoxy magnetic beads, affinity ligand, and small molecule amino compound is 1:1:1 to 10.
Citation Information
Patent Citations
Endotoxin adsorption material for curing endotoxemia
CN101157018A
Method for treating endotoxemia by using anion-exchange resin as adsorbent
CN101642591A
Magnetic anion exchanger and application of magnetic anion exchanger as endotoxin adsorption medium
CN102423721A
Adsorbent for removing endotoxin by blood perfusion and preparation method thereof
CN103406111A
Endotoxin adsorption material for blood purification and preparation method and application of endotoxin adsorption material for blood purification
CN105664868A